Penerapan Student Center Learning Untuk Peningkatan Kemampuan Berpikir Kritis Mahasiswa Tadris Matematika Pada Mata Kuliah Kalkulus Integral - Herawati, Ratna; Astuti, Wiwin; Purnamasari, Anita (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
Lectures are basically a relationship between lecturers and students with the purpose of lectures being the achievement of Course Learning Outcomes. Mathematics Education students have a challenge regarding the mindset that courses in the Mathematics Education study program are not easy so that they require critical logical mathematical thinking skills. Critical thinking skills were needed because they have an impact on learning outcomes. The lecture process that is centered on lecturers is one of the causes of passive classes and low critical thinking skills of students. A learning approach was needed that could foster critical thinking skills of students. This study was aims to improve the critical thinking skills students of Mathematics Education in the Integral Calculus course through the application of Student Center Learning. The method of qualitative research is the research of classroom action, the technique of data collect is non-test, namely through observation, data sources from observation sheets and students. The research results show that there is an increase in indicators of critical thinking skills before and after the action. Before the action, students can identify problems by 15% and after the action becomes 50%. Students can analyze problems, before the action by 20% and after the action 60%. Students can solve problems, before the action 15% and after the action 65%. Students can draw conclusions before the action 25%, after the action 70%. From the research results and discussion, it could be concluded that practice the Student Center Learning could improve the critical thinking skills the students of Mathematics Education in the Integral Calculus Course